The Story of Luxury Products and the (Broken) Promise of Superior Product Quality in a World of Prestige for the Masses - CALBOLI, Irene (Institutional Knowledge at Singapore Management University, 2015)
This chapter examines the legal protection of luxury trademarks. These marks are often protected not only against trademark infringement, but also against trademark dilution because they are considered to be famous marks. More specifically, the chapter addresses the relationship between this protection and the promise of superior quality that luxury products generally convey to the public. It considers the evolution of the luxury industry and its progressive shift away from products of superior quality toward embracing also a culture of prestige for the masses, or “masstige”—certainly a more profitable aim, but one less focused on a tradition of superior product quality and exclusivity, and in turn less deserving of anti-dilution protection.